1993
DOI: 10.1161/01.res.73.3.569
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of helix-loop-helix proteins in cardiac gene expression.

Abstract: Because helix-loop-helix (HLH) transcription factors appear to play an important role in mesodermal development, we have investigated the potential role of these factors in cardiac gene expression. HLH proteins interact with DNA at consensus "E-box" sites and may be tissue specific or more widely expressed. We have examined cardiac cells for expression and regulation of widely expressed factors Panl/Pan2 and the inhibitor of differentiation (Id) by RNase protection analysis. vectors with E-box-containing promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…In addition, forced expression of Id has been shown to inhibit tissue-specific gene expression or differentiation of a variety of cell types (1, 10 -12). Previous reports have demonstrated that Id levels are high in embryonic hearts and decrease after birth (13)(14)(15). Such a shift in Id expression is consistent with its role as an inhibitor of differentiation.…”
supporting
confidence: 78%
“…In addition, forced expression of Id has been shown to inhibit tissue-specific gene expression or differentiation of a variety of cell types (1, 10 -12). Previous reports have demonstrated that Id levels are high in embryonic hearts and decrease after birth (13)(14)(15). Such a shift in Id expression is consistent with its role as an inhibitor of differentiation.…”
supporting
confidence: 78%
“…These include genes involved in sarcomeric function, 23,25 like ␣-actin, troponin I, and myosin light chain 2, as well as a number of genes involved in ATP production, 26 including a heart-and muscle-specific isoform of ADP/ATP translocase, the Reiske iron-sulfur protein (a ubiquitously expressed electron transport chain component), and a muscle isozyme of phosphofructokinase. The precise molecular mechanism underlying this inhibition of gene transcription is unknown but has been suggested to be linked to a reduction of myoD activity 27 ; however, studies from Evans et al 28 indicate that overexpression of Id, a suppressor of myoD activity, in cardiac myocytes does not result in significant suppression of the ANP gene promoter, implying that the mechanism underlying doxorubicin-dependent inhibition of this gene may be distinct from that governing inhibition of other myogenic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In transient assays, the MLC-2v promoter is not downregulated by cotransfection with an Id expression vector that negatively regulates the activity of E-box-dependent promoters in the cardiac and skeletal muscles (21). Taken together, there is increasing evidence that cardiac muscle specificity for the MLC-2v promoter does not rely on a single site and requires combinatorial interactions between a variety of regulatory elements located within the 250-bp MLC-2v promoter fragment.…”
mentioning
confidence: 99%
“…Given the central role of a family of basic helix-loop-helix (HLH) myogenic determination genes (the MyoD, myf-5, myogenin, and myf-6/MRF4/herculin genes) in skeletal myogenesis, a number of laboratories have examined the potential role of basic HLH proteins in the control of cardiac myogenesis. Cardiac muscle cells express the ubiquitous basic HLH protein E12/E47 and are permissive for the actions of MyoD (21,33). Furthermore, a number of cardiac promoters have been documented to acquire an intact E-box site to maintain optimal activity in transient assays in cultured cardiac muscle cells (35).…”
mentioning
confidence: 99%